2011
DOI: 10.1002/joc.2315
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐seasonal variability over the northeastern highlands of Tanzania

Abstract: ABSTRACT:The intra-seasonal variability of rainfall over the northeastern Highlands (NEH) of Tanzania during the March, April, May (MAM) rainfall season and associated circulation anomalies have been studied for selected wet and dry years. Station rainfall data were used to extract the onset, peak, and cessation dates of the rainfall season and National Center for Atmospheric Research/National Center for Environmental Prediction (NCEP/NCAR) data were used to study the atmospheric circulation features associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…During the long rains seasonal rainfall is only moderately correlated with those statistics but is strongly correlated with the number of extreme wet events [Pohl and Camberlin, 2006a]. Farther south, in Tanzania, rainfall during the long rains is correlated with both the onset and end and thus with season length [Kijazi and Reason, 2012]. Camberlin and Okoola [2003] found that a late onset of the long rains is correlated with positive sea level pressure over the Indian Ocean and negative sea level pressure over the South Atlantic.…”
Section: Seasonal Versus Intraseasonal Rainfall Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the long rains seasonal rainfall is only moderately correlated with those statistics but is strongly correlated with the number of extreme wet events [Pohl and Camberlin, 2006a]. Farther south, in Tanzania, rainfall during the long rains is correlated with both the onset and end and thus with season length [Kijazi and Reason, 2012]. Camberlin and Okoola [2003] found that a late onset of the long rains is correlated with positive sea level pressure over the Indian Ocean and negative sea level pressure over the South Atlantic.…”
Section: Seasonal Versus Intraseasonal Rainfall Characteristicsmentioning
confidence: 99%
“…During the long rains seasonal rainfall is only moderately correlated with those statistics but is strongly correlated with the number of extreme wet events [ Pohl and Camberlin , ]. Farther south, in Tanzania, rainfall during the long rains is correlated with both the onset and end and thus with season length [ Kijazi and Reason , ].…”
Section: Intraseasonal Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Kijazi and Reason [13] found that increased fetch of lowlevel moisture flux anomalies from the Congo basin and the tropical Indian Ocean can result in the increase in MAM rainfall over Tanzania. Meanwhile, Nicholson [14][15][16] noted that the intensity and location of rainfall over the eastern Africa are strongly associated with the meridianally aligned ITCZ into which the humid south Atlantic air-masses converge with the Indian Ocean trade winds.…”
Section: Introductionmentioning
confidence: 99%
“…Research collaborations between other areas of skill similar to southern Africa but with varying human development levels have, for example, recently taken place. Funded studies of rainfall variability over respectively Kenya (Gamoyo et al, 2015) and Tanzania (Kijazi and Reason, 2012) involved scientists from both these countries in east equatorial Africa and southern Africa. Moreover, although northern and northeastern Brazil have seasonal forecast skill levels statistically different from southern Africa but with similar HDI values, important funded research collaboration resulted in an improved understanding of the climate system affecting both regions (Grimm and Reason, 2011;.…”
Section: F I G U R E 1 Median and Mean Correlations (Pearson Andmentioning
confidence: 99%